Metabolic adaptation in hypoxia and cancer. (1st April 2021) - Paredes, Felipe; Williams, Holly C.; San Martin, Alejandra
Abstract: The ability of tumor cells to adapt to changes in oxygen tension is essential for tumor development. Low oxygen concentration influences cellular metabolism and, thus, affects proliferation, migration, and invasion. A focal point of the cell's adaptation to hypoxia is the transcription factor HIF1α (hypoxia-inducible factor 1 alpha), which affects the expression of specific gene networks involved in cellular energetics and metabolism. This review illustrates the mechanisms by which HIF1α-induced metabolic adaptation promotes angiogenesis, participates in the escape from immune recognition, and increases cancer cell antioxidant capacity. In addition to hypoxia, metabolic inhibition of 2-oxoglutarate-dependent dioxygenases regulates HIF1α stability and transcriptional activity. This phenomenon, known as pseudohypoxia, is frequently used by cancer cells to promote glycolytic metabolism to support biomass synthesis for cell growth and proliferation. In this review, we highlight the role of the most important metabolic intermediaries that are at the center of cancer's biology, and in particular, the participation of these metabolites in HIF1α retrograde signaling during the establishment of pseudohypoxia. Finally, we will discuss how these changes affect both the development of cancers and their resistance to treatment. Highlights: Synthesis and degradation of intermediate metabolites during normal physiology and cancer. Role of metabolites during metabolic adaptation to cancer and hypoxia. Role of oncometabolites on tumor growth.